Sustained censorship in ET (2026-05) (Ethiopia) - Voidly (2026)
CRITICAL severity censorship detected in Ethiopia. Confidence: 72%. Data sourced from OONI.
Censorship Incident ID: ET-2026-0099
Keywords: censorship; ET; censorship; critical